COVID-19 infection prevention and control program for aged care providers: a quasi-experimental study of Telegram-based training - Lee, Wan Ling; Jayaveloo, Vimala Devi; Chai, Sen Tyng; Ibrahim, Rahimah; Abdul Mulud, Zamzaliza (Routledge, 2024)
Given the high turnover of care workers in residential aged care facilities, continuous training on infection prevention and control (IPC) remains essential even after the COVID-19 pandemic. This study examined the impact of a Telegram-based training on aged care providers’ IPC knowledge, attitudes, self-efficacy. A two-arm, pre-post quasi-experimental study with repeated measures at week 2 (T1) and week 4 (T2) was conducted for seventy-two (72) participants from 14 residential aged care facilities in Malaysia, with 60 completing the study (30 per arm). All instructional activities and data collection for both groups were delivered through Telegram. The intervention group received a 2-day synchronous workshop (3 h/day) alongside e-materials for a 10-unit IPC module. Primary outcomes were measured using a knowledge test, COVID-19 Elderly Caregiver Questionnaire (attitude component), and an adapted General Self-Efficacy Scale. Telegram’s acceptability was also assessed using an adapted Technology Acceptance Model questionnaire. Results showed that the intervention group had a faster knowledge transfer (91.3%–93.5%; T0-T2 = ∆22.9; p ≤.002;), higher knowledge scores (∆7.2–16; p ≤.002; large effect sizes 0.9–1.7), and a small-to-modest increments in self-efficacy (∆13.2; p =.002) and attitude (∆5.2; p =.045). Integrating synchronous sessions into an online program improved knowledge transfer, enhanced self-efficacy and promoted positive attitudes by enabling real-time interpersonal communication and instant feedback. Telegram proved effective for mobile learning in aged care settings with limited resources.